The Influence of Leadership, Competence, Work Environment, and Work Culture on Employee Performance - Dita Raisa; Hary Sulaksono; Suwignyo Widagdo (Innovation Business Management and Accounting Journal, 2024)
This study aims to analyze the influence of leadership, employee competence, work environment, and organizational culture on employee performance, both partially and simultaneously, at the Office of Harbourmaster and Port Authority (KSOP) Panarukan Situbondo. The population in this study consists of all employees, with a saturated sample technique using 41 respondents. The analytical method used is multiple linear regression analysis. Based on the analysis results, leadership and work environment have a significant partial influence on employee performance. The variables of competence and organizational culture do not have a partial influence on employee performance. However, leadership, employee competence, work environment, and organizational culture have a simultaneous influence on employee performance. The conclusion of this study is that each indicator of leadership, employee competence, work environment, organizational culture, and employee performance plays an important role in improving employee performance. By utilizing the results of this research, the author, academic institutions, and the leadership of the Harbourmaster and Port Authority (KSOP) Panarukan Situbondo can make better and more strategic decisions in employee management and organizational development.